UKRAINIAN REFUGEES IN THE EU: A NEW MIGRATION CRISIS? - Olga Yu. Potemkina (Научно-аналитический вестник Института Европы РАН, 2022)
The article analyses the prerequisites for a new migration crisis that may break out in the European Union due to an unprecedented influx of migrants. The author notes that the EU has been preparing for emergencies of this kind and has succeeded in a number of initiatives. The Council took a quick decision to activate the 2001 «Temporary Protection Directive», the Commission established a «solidarity platform» to exchange information about arriving people from Ukraine, the EU Agencies used their new powers to take more active actions to accept «temporarily protected» and provide them with the necessary means for living, medical care, access to education. However, the author points out that the main challenges for the EU and the Member States are still ahead. The principals of the new arrivals’ distribution among Member States have not been set. The «solidarity mechanism», which the countries of Central and Eastern Europe have opposed more actively than the others, has not been agreed within the framework of the Pact of Migration and Asylum. The beginning of migrants’ summer travel season from Africa and the Middle East may aggravate the situation. The author believes that although it is too early to talk about a new migration crisis, the lack of resources and infrastructure to accept a new migration wave does not contribute to strengthening the solidarity of the Member states and can entail negative consequences.